2011
DOI: 10.1371/journal.pone.0017160
|View full text |Cite
|
Sign up to set email alerts
|

The IL23R R381Q Gene Variant Protects against Immune-Mediated Diseases by Impairing IL-23-Induced Th17 Effector Response in Humans

Abstract: IL-23 and Th17 cells are key players in tissue immunosurveillance and are implicated in human immune-mediated diseases. Genome-wide association studies have shown that the IL23R R381Q gene variant protects against psoriasis, Crohn's disease and ankylosing spondylitis. We investigated the immunological consequences of the protective IL23R R381Q gene variant in healthy donors. The IL23R R381Q gene variant had no major effect on Th17 cell differentiation as the frequency of circulating Th17 cells was similar in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
162
1
4

Year Published

2011
2011
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 233 publications
(174 citation statements)
references
References 41 publications
7
162
1
4
Order By: Relevance
“…Notably, rs9988642 is in strong LD with the rs11209026 chr1.hg19.g.67705958G4A variant, 7 which specifies glutamine at residue 381 in the IL-23 receptor, is associated with reduced risk of psoriasis, and abrogates signaling through the receptor. 50,51 In conclusion, we provide evidence for the existence of multiple signals in previously known loci associated with psoriasis, replicating and extending the findings of other fine-mapping studies in a largely independent sample, thereby refining the candidate regions for each association signal. The MHC region explains more variance than all other loci combined, and even the secondary MHC signal explains more variance than any other variant (or locus).…”
Section: Discussionsupporting
confidence: 82%
“…Notably, rs9988642 is in strong LD with the rs11209026 chr1.hg19.g.67705958G4A variant, 7 which specifies glutamine at residue 381 in the IL-23 receptor, is associated with reduced risk of psoriasis, and abrogates signaling through the receptor. 50,51 In conclusion, we provide evidence for the existence of multiple signals in previously known loci associated with psoriasis, replicating and extending the findings of other fine-mapping studies in a largely independent sample, thereby refining the candidate regions for each association signal. The MHC region explains more variance than all other loci combined, and even the secondary MHC signal explains more variance than any other variant (or locus).…”
Section: Discussionsupporting
confidence: 82%
“…This suggests that IL-23R function is altered by the polymorphism resulting in decreased IL-17A 15 Furthermore, recent functional data is in keeping with our results with inhibition of IL-23-mediated IL-17A production in carriers of the minor allele. 23 Despite the observed difference in IL-17A in the different IL-23R genotypes, there was no alteration in IL-21 or IL-22 serum concentrations in patients with the major or minor IL-23R genotype. Nor was there any significant difference in the concentrations of the other non-Th 17 cytokines examined associated with the IL23R SNP.…”
Section: à5mentioning
confidence: 87%
“…Indeed, a survey by Di Meglio and colleagues (Di Meglio et al 2011). suggested that IL-23R RQ381 exerted its protective effects by attenuation of IL-23-induced T H 17 functions (IL-17A production) without interfering with T H 17 differentiation (Pidasheva et al 2011).…”
Section: R381q Polymorphism: Mechanisms Of Actionmentioning
confidence: 99%